The Use of Clitics In Novel “Murder on The Orient Express” By Agatha Christee - Dewi Sri Kuning; Rulik Setiani; Ana Sintia; Erdi Saputra; Adinda Fitri; Mira Zentia; Desi Lusiana (Universitas Muhammadiyah Kotabumi, 2022)
Clitics are words or parts of words that are structurally depend on neighboring words (it is the host) and cannot stand alone. The objectives of the research are 1) to investigate the types of clitics in the Novel “Murder on the Orient Express” by Agatha Crhistee. 2) to investigate the dominant types of clitics in the novel “Murder on the Orient Express” by Agatha Crhistee. This research used qualitative descriptive method and the instrument used was the researchers. The data of this research is taken from the novel “Murder on the Orient Express” by Agatha Christee. The data analysis technique used is Miles and Huberman technique, the steps are: data reduction, data display, and drawing conclusion and verification. From the research results obtained that the researchers found 699 clitics. There are 22 proclitics and 677 enclitics. Proclitic only has two kinds (o') and (d'). While enclitic has eight kinds, namely ('m), ('re), ('ll), ('ve), ('d), ('s), (n't), and genetive ('s) and the percentage shows that enclitic is 96.85% greater than the proclitic is 3.15%. So it can be concluded that enclitic is the most dominant used in novel Murder on the Orient Express by Agatha Christee.